Problems of regional innovation strategy forming - I. M. Golova (Экономика региона, 2010)
The author considered problems and contradictions of modern innovation policy in Russia. It is shown, that at present time regions are removed from management of science-technical complex and spatial priorities are not produced. It is a serious factor of risk for conservation perspectives of innovation development for Russia. With taking into account of world experience main districts of rise effects regional police were formulated. It is underlined, that creation conditions for transformation of regional authorities in active subjects of innovation policy is necessary condition for building vital innovation system. It is shown, that state innovation policy must be constructed at combination of next principles: a) support science-technical potential of regions — generators of innovation and creation conditions for its realization; b) using of innovations for evening-out disproportions of social-economic development between regions; c) widening powers and financial possibilities of regions at management of innovation climate. Methodical approaches for making effective mechanisms of management of innovation processes of territory are opened. Typology of Russian regions with high and middle degree of innovation climate is proposed, which takes level of science and innovation potential of territory and also degree of comfort of social-economic conditions for development of innovation activity are offered. Peculiarities of innovation strategy for different types of regions are defined. This typology may be used for substantiation spatial priorities of innovation strategy of Russia.